MANAJEMEN PENILAIAN KINERJA DOSEN DALAM PENINGKATAN MUTU AKADEMIK DI IAINU TUBAN - Rustya, Dian (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2022)
The purpose of this study was to determine the basis of lecturer performance appraisal at Institut Agama Islam Nahdlatul Ulama (IAINU) Tuban and how the process of lecturer performance appraisal at Institut Agama Islam Nahdlatul Ulama (IAINU) Tuban. The research method used in this research is qualitative method with descriptive analysis method. From the research results, it is known that the performance assessment of lecturers at the Institut Agama Islam Nahdlatul Ulama (IAINU) Tuban is based on 5 aspects, namely educational aspects, supporting aspects, research aspects, aspects of community service, and aspects of work behavior in the odd semester of the 2021/2022 academic year. The assessment results show that there are several aspects of performance that get very good results such as aspects of research and community service, there are also aspects that show poor results, namely the supporting aspects.